Determinação e caracterização de minerais pesados em amostras coletadas em Itarana, Pará - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2007)
The determination and characterization of heavy minerals in the samples entitled: tower II, tower III, tower IV, hut, hut II, sandstone and beach, constitute the first stage of a broader process that aims to know the geochemical characteristics of the southwestern platform of Itarana island, located between Bragança and Salinas, on the coast of the salty Paraense. The knowledge of these geochemical characteristics will contribute to a better understanding of the northeast Para coast, bringing subsidies for its integrated study. After literature review and seminar presentation, the laboratory activities started with the crushing of the geological material, previously collected by the mentors, and its washing with the help of metallic sieves (0.063mm) and ultrasound basin. After drying in an oven (50°C), two fractions(x) of the grains were separated: 0.250mm > x > 0.125mm and 0.125mm > x > 0.063mm. Metal sieves of 0.250, 0.125 and 0.063 mm were used to separate the fractions. Because of its high density (d = 2.89), the bromoform liquid was used to separate the heavy minerals from the light minerals, enabling the heavy minerals to be deposited and easily separated from the dip, and then used to produce slides, which will be taken to the petrographic microscope for observation of the minerals. The slides are currently being observed under a petrographic microscope so that the heavy minerals can be identified and characterized.
Determination and characterization of heavy minerals in samples collected in Itarana, Pará
Keywords: Itarana; Geoquímicas; Minerais; CNPQ::CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::METALOGENIA